2015
DOI: 10.1111/tbed.12311
|View full text |Cite
|
Sign up to set email alerts
|

Constant Hepatitis E Virus (HEV) Circulation in Wild Boar and Red Deer in Spain: An Increasing Concern Source of HEV Zoonotic Transmission

Abstract: Hepatitis E is a viral zoonosis that affects multiple hosts. The complete dynamics of infection in wildlife are still unknown, but the previous fact facilitates the maintenance and circulation of the virus, posing a risk to human health in the case of meat consumption from susceptible animals. In Spain, it has been shown how domestic pigs, cattle and wildlife (i.e. wild boar and red deer) clearly interact in hunting farms, generating a complex epidemiological situation in terms of interspecies pathogen transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
85
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 36 publications
9
85
3
Order By: Relevance
“…Surprisingly, the seroprevalence detected in closed systems was significantly lower than the one detected in open systems. Despite the specificities of the different pig breeding systems, the overall seroprevalence observed in our limited sample of Corsican pigs obtained during the first year of life (41.70%), remains comparable to the one reported in other European countries [6,30,31]. A possible explanation is that despite in open systems the density of pigs is likely to be lower than in intensive pig farms, animals in open or semi-open systems tend to concentrate around food and water points reaching densities that are sufficiently high to allow regular exposure to most of the herd through the contamination of food and water.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Surprisingly, the seroprevalence detected in closed systems was significantly lower than the one detected in open systems. Despite the specificities of the different pig breeding systems, the overall seroprevalence observed in our limited sample of Corsican pigs obtained during the first year of life (41.70%), remains comparable to the one reported in other European countries [6,30,31]. A possible explanation is that despite in open systems the density of pigs is likely to be lower than in intensive pig farms, animals in open or semi-open systems tend to concentrate around food and water points reaching densities that are sufficiently high to allow regular exposure to most of the herd through the contamination of food and water.…”
Section: Discussionsupporting
confidence: 83%
“…Several authors have described an association between densities of wild boars and HEV seroprevalence [4,31,33,34]. In our study, data on densities of wild boar were not available.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The presence of HEV in roe deer was studied only in the Netherlands, Hungary, and Poland. In the Netherlands, no HEV RNA was detected in eight analyzed roe deers (Rutjes et al 2010) and no sera resulted positive in roe deer from Poland (Larska et al 2014 Kukielka et al (2015) showed that 16.05 % samples from red deer were HEV positive by real-time RT-PCR in Spain. All European hare (Lepus europeaus) samples tested negative for HEV in the present study.…”
Section: Discussionmentioning
confidence: 97%
“…HEV has been found in domestic pigs, wild boar, deer, mongoose and bivalves [9][10][11][12]. The most likely route of transmission to humans is consuming raw or undercooked meat of infected wild animals such as meat of boars and deers and domestic animals such as pigs [13][14][15].…”
Section: Discussionmentioning
confidence: 99%